Two new species of Idris Foerster (Hymenoptera: Platygastridae) from Southeastern Brazil, parasitoids of Argyrodes elevatus Walckenaer (Araneae: Theridiidae) and Scytodes sp. (Araneae: Scytodidae) - Margaría, Cecilia B. (2015)
In this study two new species of Idris Foerster (Platygastridae) are described and illustrated: I. argyrodes sp. nov. and I. scytodes sp. nov., from specimens reared from eggs of the spider species Argyrodes elevatus Walckenaer (Theridiidae) and Scytodes sp. (Scytodidae) collected in Minas Gerais State, Brazil. Scytodidae is anew host family for Idris.